Effect of pile driving on pore pressure, shear strength and bearing capacity - Veeraphol Srimahachota; Brenner, R.P.; Campbell, K.V.; Holmberg, Soren; The Royal Netherlands Government (Bangkok : Asian Institute of Technology, 1978)
The effect of pile driving on pore pressure and shear strength was investigated at a site where the subsoil consists of an 8 m _thick deposit of soft clay underlaid by stiff clay. Two pile groups were installed. One group consisted of 16,7.8 m long piles while the other group included 9,11.5 m long piles. All the piles were timber piles with an average diameter of 20 cm. Pore pressure measurements were carried out both within the pile groups and at different distances from the group. The shear strength of the subsoil was measured by means of field vane tests before and after the installation of the pile groups. Finally, a few load tests of the piles were carried out at different times after the piles were driven in order to evaluate the adhesion factor.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Piling (Civil engineering) -- Testing